2006
DOI: 10.1021/la061300i
|View full text |Cite
|
Sign up to set email alerts
|

On the Binding of Calcium by Micelles Composed of Carboxy-Modified Pluronics Measured by Means of Differential Potentiometric Titration and Modeled with a Self-Consistent-Field Theory

Abstract: We perform differential potentiometric titration measurements for the binding of Ca2+ ions to micelles composed of the carboxylic acid end-standing Pluronic P85 block copolymer (i.e., CAE-85 (COOH-(EO)26-(PO)39-(EO)26-COOH)). Two different ion-selective electrodes (ISEs) are used to detect the free calcium concentration; the first ISE is an indicator electrode, and the second is a reference electrode. The titration is done by adding the block copolymers to a known solution of Ca2+ at neutral pH and high enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In addition, the width of the transition region (from the start of micellization to its completion) is concentration dependent in P85 solutions: with increasing concentration, the width increases from 1.0 C to 5.2 C. In CAE85 solutions, the transition width does not change signicantly and it uctuates around 1.0 C (Table 1) for concentrations between 5 wt% and 15 wt%. The micellization parameters obtained in this work compare favorably with the report of Lauw et al: 41 the CMT of approx. 20 C for the concentration of about 2 wt% at ionic strength of 5 Â 10 À3 M and at pH ¼ 7.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the width of the transition region (from the start of micellization to its completion) is concentration dependent in P85 solutions: with increasing concentration, the width increases from 1.0 C to 5.2 C. In CAE85 solutions, the transition width does not change signicantly and it uctuates around 1.0 C (Table 1) for concentrations between 5 wt% and 15 wt%. The micellization parameters obtained in this work compare favorably with the report of Lauw et al: 41 the CMT of approx. 20 C for the concentration of about 2 wt% at ionic strength of 5 Â 10 À3 M and at pH ¼ 7.…”
Section: Discussionsupporting
confidence: 89%
“…The results exhibited the expected collapse of the layer with increased ionic strength at low grafting density and the re-entrant phenomena of stretched chains with increased ionic strength at high grafting density. In turn, 1:1 binding of Ca to micelles composed by carboxylic acid end-standing Pluronic P85 block copolymers was studied both experimentally by differential potentiometric titration measurements and by SF-SCF theory [ 149 ]. The authors included both acid–base equilibrium and ion condensation reactions into the model, and found that Ca ions bind both electrostatically and specifically.…”
Section: Applicationsmentioning
confidence: 99%
“…Research on self-assembled amphiphiles in an aqueous solvent has been intensified in the last couple of decades [1][2][3][4][5][6][7][8][9]. Amphiphiles consist of both hydrophobic and hydrophilic parts and they form aggregates (micelles) with particular morphologies in a selective solvent.…”
Section: Introductionmentioning
confidence: 99%